2014
DOI: 10.1785/0120130279
|View full text |Cite
|
Sign up to set email alerts
|

Validating Accuracy of Rayleigh-Wave Dispersion Extracted from Ambient Seismic Noise Via Comparison with Data from a Ground-Truth Earthquake

Abstract: In order to validate the accuracy of estimated Green's functions (EGFs), which are widely used in ambient seismic noise tomography, a broadband seismograph was installed in the epicentral area of an M 5 earthquake, with ground-truth location from Interferometric Synthetic Aperture Radar observations. EGFs between this station and permanent stations are compared with surface waves excited by the earthquake. The group velocity dispersion measured from EGFs at large interstation distances (∼1000 km or longer) are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Instead, he proposed an alternative explanation based on a stationary phase approximation and assuming waves traveling along a single path. Validity of EGF has also been demonstrated via comparing them with earthquake surface waves recorded by stations near the seismic source or with synthetic seismograms after taking into account source depth and focal mechanisms (Bao et al, 2014;Denolle et al, 2013;Shapiro & Campillo, 2004;Xie et al, 2016). Many other derivations have illuminated the relation between NCF and EGF by adopting the assumptions of homogeneous media and a uniform noise source distribution (e.g., Roux et al, 2005;Sanchez-Sesma & Campillo, 2006;Sato, 2009;Tanimoto, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, he proposed an alternative explanation based on a stationary phase approximation and assuming waves traveling along a single path. Validity of EGF has also been demonstrated via comparing them with earthquake surface waves recorded by stations near the seismic source or with synthetic seismograms after taking into account source depth and focal mechanisms (Bao et al, 2014;Denolle et al, 2013;Shapiro & Campillo, 2004;Xie et al, 2016). Many other derivations have illuminated the relation between NCF and EGF by adopting the assumptions of homogeneous media and a uniform noise source distribution (e.g., Roux et al, 2005;Sanchez-Sesma & Campillo, 2006;Sato, 2009;Tanimoto, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of inhomogeneous media, Wapenaar (2004) derived a proof of retrieving EGF based on reciprocal theory. Validity of EGF has also been demonstrated via comparing them with earthquake surface waves recorded by stations near the seismic source or with synthetic seismograms after taking into account source depth and focal mechanisms (Bao et al, 2014;Denolle et al, 2013;Shapiro & Campillo, 2004;Xie et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To validate the group velocity measurement from ambient noise, we also compared it with the group velocity dispersion computed from an earthquake of magnitude five in the proximity of GARM recorded at GUGE (Figure S1d in Supporting Information S1). Both the dispersion curves are largely consistent with each other, although there are mismatches at 20-30 s, and 45-60 s. This difference, which is around 2% of the event dispersion, probably indicates inadequate source parametrization of the event, low SNR of the event and/or noise dispersion, and inhomogeneity of the ambient noise wavefield (see F. Bao et al [2014] for a detailed discussion). After applying the selection criteria mentioned earlier, we are left with 9,794 (out of 22,958 initial) inter-station dispersion measurements with Rayleigh wave group velocity data from period 5-60 s for further analysis.…”
Section: Ambient Noise Analysismentioning
confidence: 54%
“…Barmin et al (2011) used Rayleigh waves retrieved from the ASN and the earthquake seismograms in order to test the new epicentral location method. Bao et al (2014) showed that the Green's functions from ASN records provide very similar Rayleigh wave group dispersion curves as earthquake records. Quattara et al 2019, obtained well correlation between Rayleigh waves estimated from the earthquake and ASN records.…”
Section: Literature Surveymentioning
confidence: 92%